Implementation Of Compensation For Land Rights For The Public Interest (Case Study Of Betoambari Airport, Baubau City) - Sunardi, Sunardi; Isnaeni, Dian; Roydatul Janna, Ghira (Universitas Islam Malang, 2025)
Abstract : The Indonesian government continues to carry out development in various fields in line with the mandate of the opening of the 1945 Constitution of the Republic of Indonesia, namely to advance the welfare of all Indonesian people. Therefore, the Indonesian government is trying to achieve this goal by carrying out public development. Development for the public interest requires land as an important aspect that supports its successful implementation. However, the problem is that the land controlled by the state is limited. Based on these circumstances, the government carries out land acquisition using land of individuals or legal entities that have been controlled for public purposes. In this case, Betoambari Airport, Baubau city, is carrying out construction, namely expanding the runway area which requires land around the airport area. The problem formulation in this thesis is, What is the process of implementing compensation for land rights for the public interest in the development of Betoambari Airport in Baubau City, what obstacles occur in the implementation of providing compensation for the development of Betoambari Airport in Baubau City, and How to Overcome Obstacles in the Implementation of Compensation provided by Betoambari Airport Development in Baubau City. This research uses empirical juridical research methods with a conceptual approach and a statutory approach, both of which are interconnected by concepts and statutory regulations. The results of the research in the implementation of providing compensation for land rights along with land acquisition for the expansion of the Betoambari Airport area in Baubau City were carried out in 2 stages, totaling 23 plots of land with a total area of 34,177 M². bank, in an effort to overcome these obstacles, the city government provides time to complete the installments of the bank loan and encourages the community involved in the loan to complete the obligations of the certificate owner.